Age-related changes in layer II immature neurons of the murine piriform cortex - Ghibaudi, Marco; Marchetti, Nicole; Vergnano, Elena; La Rosa, Chiara; Benedetti, Bruno; Couillard-Despres, Sebastien; Farioli-Vecchioli, Stefano; Bonfanti, Luca (Frontiers in Cellular Neuroscience, 2023)
The recent identification of a population of non-newly born, prenatally generated "immature" neurons in the layer II of the piriform cortex (cortical immature neurons, cINs), raises questions concerning their maintenance or depletion through the lifespan. Most forms of brain structural plasticity progressively decline with age, a feature that is particularly prominent in adult neurogenesis, due to stem cell depletion. By contrast, the entire population of the cINs is produced during embryogenesis.Then these cells simply retain immaturity in postnatal and adult stages, until they "awake" to complete their maturation and ultimately integrate into neural circuits. Hence, the question remains open whether the cINs, which are not dependent on stem cell division, might follow a similar pattern of age-related reduction, or in alternative, might leave a reservoir of young, undifferentiated cells in the adult and aging brain. Here, the number and features of cINs were analyzed in the mouse piriform cortex from postnatal to advanced ages, by using immunocytochemistry for the cytoskeletal marker doublecortin. The abundance and stage of maturation of cINs, along with the expression of other markers of maturity/immaturity were investigated. Despite a marked decrease in this neuronal population during juvenile stages, reminiscent of that observed in hippocampal neurogenesis, a small amount of highly immature cINs persisted up to advanced ages. Overall, albeit reducing in number with increasing age, we report that the cINs are present through the entire animal lifespan.